2013
DOI: 10.1104/pp.113.217547
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid- and Stress-Induced Highly Proline-Rich Glycoproteins Regulate Root Growth in Rice

Abstract: In the root of rice (Oryza sativa), abscisic acid (ABA) treatment, salinity, or water deficit stress induces the expression of a family of four genes, REPETITIVE PROLINE-RICH PROTEIN (RePRP). These genes encode two subclasses of novel proline-rich glycoproteins with highly repetitive PX 1 PX 2 motifs, RePRP1 and RePRP2. RePRP orthologs exist only in monocotyledonous plants, and their functions are virtually unknown. Rice RePRPs are heavily glycosylated with arabinose and glucose on multiple hydroxyproline resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 83 publications
1
36
0
Order By: Relevance
“…Moreover, Glyma.10G080000 (in R‐M18) encodes a hydroxyproline‐rich glycoprotein family protein that is a major structural protein in the cell wall (Table S2). This gene has been shown to be induced by ABA and salt stress in rice (Tseng, Hong, Yu, & Ho, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Glyma.10G080000 (in R‐M18) encodes a hydroxyproline‐rich glycoprotein family protein that is a major structural protein in the cell wall (Table S2). This gene has been shown to be induced by ABA and salt stress in rice (Tseng, Hong, Yu, & Ho, ).…”
Section: Resultsmentioning
confidence: 99%
“…They are involved in cell organization, oxidative stress, photosynthesis, and defense responses. However, some of them are known to be regulated by ABA (Ton et al, 2009;Kar, 2011;Sreenivasulu et al, 2012;Tseng et al, 2013). It is possible that many of these genes in this group may be transcriptionally activated by ABA at a later time point or higher ABA concentration than we used.…”
Section: Discussionmentioning
confidence: 99%
“…This class was checked for Pro-rich motifs from mammals and other organisms, and no motifs were found to be well represented. Some plant sequences similar to rice OsRePRP1 (Tseng et al, 2013) and AtPRP10 (Rashid and Deyholos, 2011) were found, with a total of 7.3% of class 24 proteins containing either an OsRePRP1 (0.5%) or an AtPRP10/AtPELPK1 (6.8%) Pro-rich motif (Table II).…”
Section: Maab Class 24: a Resource To Mine For New Idps And Prp Motifsmentioning
confidence: 99%
“…4E). AtPELPK1 is localized to the cell wall (Rashid, 2014) and is an IDP, yet it remains uncertain if it and OsRePRP1 (Tseng et al, 2013) are bona fide Hyp-containing glycoproteins. Determining if and where Pro-to-Hyp modification (and subsequent glycosylation) occurs in the novel motifs identified within class 24 will require experimental approaches such as in planta expression.…”
Section: Maab Class 24: a Resource To Mine For New Idps And Prp Motifsmentioning
confidence: 99%